Os modos de dizer e de fazer (d) a convivência: enunciados e invenções de semiárido. - Sá, Almair Morais de (2012)
The performance of some institution in Brazilian Semi-arid followed the production, distribution and sell from several materials which try to propagate the enunciation knowledges and sayings from convenience. The purpose of this work is to questionate the discourse of acquaintance with the Semi-arid which is transmitted by the cordéis and songs aiming to apprehend how they reveal through the ways of saying and doing these discourse enunciate images and conceptions about the Semi-arid, its people and cultural practices as well as which cultural policies it envolves and what historical culture its produces. The data used were the following: the cordéis produced by ASA (Articulação no Semiárido), and the ones produced by INSA (Instituto Nacional do Semiárido) as well as the Belo Sertão CD: The acquaintance with the Semi-arid by means of songs. In this work the contribution from Michel Foucault is used. The results shows that these productions serves as instruments to institutionals discourses based on communication strategies although they do not limits themselves to promotion of acquaintance in the Semi-arid. The results also demonstrate that these discourses reveal complex procedures of social, economic and political exclusions operation that mobilize past, present and future to show interpretation about the Semi-arid its people and cultural practices. It also reveals that the acquaintances‟ discourses enunciate knowledges and practices to be observed. By means of these questions it was determined that the vinvulation of this study is associated with Regional History research and the area of concentration is History and Historical Culture.